An analysis on teachers' and teacher candidates' usage of internet based materials and awareness of learning objects - Yeni, Sabiha (ELSEVIER SCIENCE BV, 2012)
21st century technology-based education enables all learners to try different learning experiences both inside and outside school. It is also a new approach which provides learners to participate in global social networks as active, creative and sophisticated individuals. Therefore, it is very important for teachers to use internet based instructional materials and learning objects during the lessons. The purpose of this study is to determine teachers' and teacher candidates' use of digital materials from the internet and their awareness of learning objects in the object repositories. In this study two different questionnaires were applied to 107 teachers and 74 teacher candidates to gather data. The findings of this study demonstrated that the most of participants used internet resources to prepare course content and materials. Also it is observed that although participants' used internet resources frequently, they did not know much about learning objects and object repositories. Consequently, it is determined that object repositories are not used as a resource during the preparation of course content.(C) 2012 Published by Elsevier Ltd. Selection and/or peer review under responsibility of Prof. Dr. Huseyin Uzunboylu
Keywords: Internet Based Materials; Learning Objects; Object Repositories; Education & Educational Research